2016
DOI: 10.1242/jcs.192211
|View full text |Cite
|
Sign up to set email alerts
|

Rnd3-induced cell rounding requires interaction with Plexin-B2

Abstract: Rnd proteins are atypical members of the Rho GTPase family that induce actin cytoskeletal reorganization and cell rounding. Rnd proteins have been reported to bind to the intracellular domain of several plexin receptors, but whether plexins contribute to the Rnd-induced rounding response is not known. Here we show that Rnd3 interacts preferentially with plexin-B2 of the three plexin-B proteins, whereas Rnd2 interacts with all three B-type plexins, and Rnd1 shows only very weak interaction with plexin-B protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…The intracellular domain of PlexinB2 can elicit RhoA activation in response to ligand stimulation, through the activity of plexin-associated Rho-GEFs, such as p190-PRG and LARG [14,18,31,32]. Indeed, we observed a reduced content of F-actin stress fibers in Sema4C-or PlexinB2depleted cells compared with controls (data not shown), which could be consistent with decreased RhoA activity.…”
Section: Sema4c/plexinb2/larg-dependent Rhoa Signaling Is Required Tosupporting
confidence: 73%
“…The intracellular domain of PlexinB2 can elicit RhoA activation in response to ligand stimulation, through the activity of plexin-associated Rho-GEFs, such as p190-PRG and LARG [14,18,31,32]. Indeed, we observed a reduced content of F-actin stress fibers in Sema4C-or PlexinB2depleted cells compared with controls (data not shown), which could be consistent with decreased RhoA activity.…”
Section: Sema4c/plexinb2/larg-dependent Rhoa Signaling Is Required Tosupporting
confidence: 73%
“…Other candidate interactors might be relevant to the functions of Rnd2 in adult-born DGNs. For example, semaphorin receptors, known as Plexins, have been implicated in AHN (Duan et al, 2014;Jongbloets et al, 2017;Mata et al, 2018;Zhao et al, 2018) and have been shown to be bound and regulated by Rnd2 in neurons and other cell types (Azzarelli et al, 2014;McColl et al, 2016;Uesugi et al, 2009). Nevertheless, whether Plexins mediate some aspects of Rnd2 action in adult newborn neurons remains unknown.…”
Section: Rnd2 Has Unique Functions In the Development Of Adult-born Dgnsmentioning
confidence: 99%
“…Plexin stimulation delivers directional cues for cell migration and axon guidance through the regulation of several small GTPases and semaphorin-plexin signalling can either be attractive or repulsive depending on the particular plexin co-receptor expressed (4,5), while nonpolarised stimulation of cells with semaphorins results in cell collapse (6). B-class plexins can interact with the GTPases Rnd1-3 (7,8), Rac (9), RhoD(10), R-Ras (7) and M-Ras (11) and regulate Rho via PDZRhoGEF/LARG (12) and p190RhoGAP (13). In addition, the plexin cytoplasmic tail contains a GTPase activating protein (GAP) domain (14) divided into two regions by a Rho Binding domain (RBD) (15) and plexins act as GAPs for Rap1B and Rap2A (16).…”
Section: Introductionmentioning
confidence: 99%